Dawn at Vesta: Testing the Protoplanetary Paradigm - Russell, C. T.; Raymond, C. A.; Coradini, A.; McSween, H. Y.; Zuber, M. T.; Nathues, A.; de Sanctis, M. C.; Jaumann, R.; Konopliv, A. S.; Preusker, F.; Asmar, S. W.; Park, R. S.; et al. (Science, 2012)
The Dawn spacecraft targeted 4 Vesta, believed to be a remnant intact protoplanet from the earliest epoch of solar system formation, based on analyses of howardite-eucrite-diogenite (HED) meteorites that indicate a differentiated parent body. Dawn observations reveal a giant basin at Vesta s south pole, whose excavation was sufficient to produce Vesta-family asteroids (Vestoids) and HED meteorites. The spatially resolved mineralogy of the surface reflects the composition of the HED meteorites, confirming the formation of Vesta s crust by melting of a chondritic parent body. Vesta s mass, volume, and gravitational field are consistent with a core having an average radius of 107 to 113 kilometers, indicating sufficient internal melting to segregate iron. Dawn's results confirm predictions that Vesta differentiated and support its identification as the parent body of the HEDs. NH-Mineral Sciences NMNH Peer-reviewed